2007
DOI: 10.1096/fj.07-8371com
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a circadian clock in mammalian photoreceptors

Abstract: Several studies have demonstrated that the mammalian retina contains an autonomous circadian clock. Dopaminergic and other inner retinal neurons express many of the clock genes, whereas some of these genes seem to be absent from the photoreceptors. This observation has led to the suggestion that in mammalian retina the circadian pacemaker driving retinal rhythms is located in the inner nuclear layer. However, other evidence points to the photoreceptor layer as the site of the mammalian retinal clock. The goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
125
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 45 publications
7
125
2
Order By: Relevance
“…It is conceivable that only under certain pathological conditions of ischemia or hypoxia, RORa becomes highly induced to exert suppression on SEMA3E to result in exacerbation of pathological neovascularization, whereas under normal developmental conditions RORa is likely expressed only at a low basal levels that are not sufficient to significantly affect Sema3E expression and developmental retinal angiogenesis. In addition to RGCs, expression of RORa was identified in retinal photoreceptors (26,27) and macrophages/microglia (25). Whereas expression of RORa was reported in human vascular cells (61,62), previously we observed only low levels of RORa expression in retinal blood vessels.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It is conceivable that only under certain pathological conditions of ischemia or hypoxia, RORa becomes highly induced to exert suppression on SEMA3E to result in exacerbation of pathological neovascularization, whereas under normal developmental conditions RORa is likely expressed only at a low basal levels that are not sufficient to significantly affect Sema3E expression and developmental retinal angiogenesis. In addition to RGCs, expression of RORa was identified in retinal photoreceptors (26,27) and macrophages/microglia (25). Whereas expression of RORa was reported in human vascular cells (61,62), previously we observed only low levels of RORa expression in retinal blood vessels.…”
Section: Discussionmentioning
confidence: 76%
“…Our previous study (25) showed that RORa is expressed in retinal macrophages and microglia and regulates pathological retinal angiogenesis by modulating SOCS3-dependent inflammation in a mouse model of oxygen-induced retinopathy (OIR), modeling retinopathy of prematurity and the proliferative aspects of diabetic retinopathy in humans. Other studies also identified RORa expression in retinal neurons, including RGCs and photoreceptors (21,26,27), yet whether RORa regulates expression of SEMA3s in the retinal neurons to affect retinal angiogenesis is not known.…”
mentioning
confidence: 99%
“…Many investigations have shown that retinal photoreceptors of vertebrates synthesize melatonin under the direct control of a circadian clock (2,3). In a few cases, the circadian pacemaker driving rhythmic melatonin synthesis has been localized to the photoreceptors themselves (2,4,5). In the retina melatonin levels are high during the night and low during the day and exposure to light during the night induces a rapid and dramatic decrease in the levels of melatonin (6,7).…”
mentioning
confidence: 99%
“…[16] Their input synchronizes the SCN to maintain the circadian rhythm near a 24 h cycle by driving the nocturnal synthesis of the pineal hormone National Journal of Physiology, Pharmacy and Pharmacologymelatonin and feedback loops to mediate clock information to the peripheral tissues and induce circadian phase, sleep, and maintenance of pupil diameter. [17,18] Hence, melanopsin which has a role in the maintenance of pupil diameter [19][20][21][22] and providing the primary environmental light input to the SCN for photoentrainment of the circadian rhythm might be affected. A constricted pupil may decrease the area of retinal illumination and increase the average latency of P100.The average decrease in pupillary diameter of 1.75 mm increases the average latency by 4.6 ms. [1] Our finding also supports the result of Jackson et al, [23] who observed the increase in P100 latency and reduction in amplitude in professional drivers with sleep deprivation.…”
Section: Discussionmentioning
confidence: 99%